2021
DOI: 10.3390/chemistry3040087
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of Fructose to 5-Hydroxymethylfurfural: Effects of Acidity and Porosity of Different Catalysts in the Conversion, Selectivity, and Yield

Abstract: There is a demand for renewable resources, such as biomass, to produce compounds considered as platform molecules. This study deals with dehydration of fructose for the formation of 5-hydroxymethylfurfural (HMF), a feedstock molecule. Different catalysts (aluminosilicates, niobic acid, 12-tungstophosphoric acid—HPW, and supported HPW/Niobia) were studied for this reaction in an aqueous medium. The catalysts were characterized by XRD, FT-IR, N2 sorption at −196 °C and pyridine adsorption. It was evident that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(105 reference statements)
2
2
0
Order By: Relevance
“…Moreover, the Brønsted acid peak of CrPO(2)/Al‐SBA‐15 had a lower wavenumber than other samples (see Figure 9B), suggesting a stronger site, leading to a higher 5‐HMF yield. The hypothesis is possible because the stronger Brønsted acid could accelerate the dehydration of fructose intermediate to 5‐HMF [53] . This observation agrees well with the presence of P−O−Cr covalent bonds in Cr(III) phosphate property, which is dominant in CrPO(2)/Al‐SBA‐15 suggested by XANES of P K‐edge.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Moreover, the Brønsted acid peak of CrPO(2)/Al‐SBA‐15 had a lower wavenumber than other samples (see Figure 9B), suggesting a stronger site, leading to a higher 5‐HMF yield. The hypothesis is possible because the stronger Brønsted acid could accelerate the dehydration of fructose intermediate to 5‐HMF [53] . This observation agrees well with the presence of P−O−Cr covalent bonds in Cr(III) phosphate property, which is dominant in CrPO(2)/Al‐SBA‐15 suggested by XANES of P K‐edge.…”
Section: Resultssupporting
confidence: 82%
“…The hypothesis is possible because the stronger Brønsted acid could accelerate the dehydration of fructose intermediate to 5-HMF. [53] This observation agrees well with the presence of PÀ OÀ Cr covalent bonds in Cr(III) phosphate property, which is dominant in CrPO(2)/Al-SBA-15 suggested by XANES of P K-edge. This explanation is consistent with Ramis et al [54] that the Brønsted acid strength of the surface PÀ OH groups increases with increasing covalency of the (PO)À M bond.…”
Section: Catalytic Activity Of Crpo/al-sba-15 On Glucose Conversion T...supporting
confidence: 87%
See 2 more Smart Citations
“…The highest yield of fructose was reached after 3 h of hydrolysis with 0.1 M HCl at 90 • C in the case of BL from S. salivarius K12. In comparison, a higher degree of hydrolysis for L. mesenteroides DSM 20343 was found after 6 h. It was observed that with increasing molarity of the HCl solution, there was a noticeable decrease in the fructose content, possibly due to fructose dehydration to hydroxymethylfurfural [80]. Moreover, the non-selectivity of HCl as a catalyst in cleavage of glycosidic linkages and weak fructose release from BL produced by Zymomonas mobilis was highlighted by Bekers et al [81] and Kennedy et al [82] as a high amount of fructooligosaccharides was observed in the final products.…”
Section: Notementioning
confidence: 86%